2019
DOI: 10.1007/s10796-019-09902-4
|View full text |Cite
|
Sign up to set email alerts
|

Value Co-Creation as a Dialectical Process: Study in Bangladesh and Indian Province of West Bengal

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 100 publications
(120 reference statements)
5
29
0
Order By: Relevance
“…Social collaboration ignites the sense of the customers for being involved in any activity related with the process of business for developing value by such co-creation activities Agarwal et al 2017;Rahman et al 2019;Chatterjee and Kar 20182020). Besides, value co-creation in the process of business by a firm is sometimes misconstrued because of the contribution of the producers' endeavour.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Social collaboration ignites the sense of the customers for being involved in any activity related with the process of business for developing value by such co-creation activities Agarwal et al 2017;Rahman et al 2019;Chatterjee and Kar 20182020). Besides, value co-creation in the process of business by a firm is sometimes misconstrued because of the contribution of the producers' endeavour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This concept increases customers' involvement in the process of coproduction by the help of sharing customers' creativity, knowledge and new ideas in the context of few needs of a firm (Zhang and Chen 2008). From the repository of knowledge, ideas as well as sense of creativity, the customers and the firm can build solid foundation of competence in the process of coproduction that helps to co-create value (Rahman et al 2019). By such sharing of knowledge through the intimate cooperation between the customers and the firm, it is possible to achieve better results compared to that achieved through the independent functioning.…”
Section: Customers' Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, the institutional approach surfaced as one of ways to implementing and assessing the outcomes, wherein the scholars called for greater need for social embeddedness in ICT based projects (Ashraf et al 2009;Brooks and Alam 2013;Lin et al 2015). According to the institutional approach, the purpose of ICT based innovations needed to arise from local conceptions of the problem of interest and be constructed considering the techno-organizational realities of the local context (Prakash and De 2015;Rahman et al 2019;Young 2018). Further, the approach suggested that development was not a problem that required fixing but a complex sociocultural process that required an emergent understanding and evolving approaches to addresses the same 9 (Jha et al 2016;Pal et al 2009).…”
Section: Institutional Approach To Assessing Ict Based Development Inmentioning
confidence: 99%
“…Second, Rahman et al (2019) investigate various technical challenges during innovation processes while using smart digital technologies in the smartphone industry in 'Value Co- Fig. 1 A Conceptual Framework for Digital Nationsfrom building blocks to themes for theoretical contribution creation as a Dialectical Process: Study in Bangladesh and India Province of West Bengal'.…”
Section: Challenges In Planning and Implementationmentioning
confidence: 99%